Variability of finger extensor muscle (m. Extensor digitorum) in human fetuses - Posłuszny, Marian (Anthropological Review, 1984)
The material for the present study consisted of 31 male and 19 female fetuses with crown-rump length ranging from 140 to 360 mm. Location of proximal attachment, relationship to neighbouring muscles, subdivision of the fleshy part and variability of tendons were observed. Percentage frequencies of observed variations are tabularized with respect to sex and asymmetry.